Asuhan Keperawatan Pada Tn. TS Dengan Diagnosis Medis SOL Intrakranial O/T (L) Temporoparietal Dd/ 1. High Grade Glioma 2. CNS Infection AKI Dd Ckd (CR 2,25) di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Sairomaito Harahap; Dudut Tanjung; Edianto Edianto; Dina Afriani; Saodah Hanim (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Background : Nurses play an important role in providing nursing care to Space Occupying Lession (SOL) patients. Nurses directly assist patients and educate them about their disease and prevent rehospitalization. During hospitalization, patients require hemodynamic stabilization monitoring, use of various monitoring and life support devices, postoperative patient care, and crisis management in the event of loss of consciousness or sedation programs. Purpose : This case study aims to perform 30ᵒ head elevation with SOL Intracranial o/t (L) Temporoparietal who has head pain. Methods : This research is a case report where the source of research data comes from the patient and the patient's family using interview techniques, observation, physical examination, and documentation study of nursing management prioritized according to the SDKI (Indonesian Nursing Diagnosis Standard), SLKI (Indonesian Nursing Outcomes Standard), and SIKI (Indonesian Nursing Intervention Standard): acute pain, decreased intracranial adaptive capacity and impaired physical mobility. Results : Decreased pain quality, increased intracranial adaptive capacity, and decreased physical mobility impairment indicate improvement in the patient's condition along with the nursing care provided. Conclusion : The results of routine nursing implementation coupled with the application of evidence-based nursing practice 30ᵒ head elevation intervention (30ᵒ head position intervention) to reduce pain along with the collaboration of pharmacological therapy administration of ketorolac injections were found to reduce the pain scale from a scale of 3 - 4 (mild - moderate) NRS to a pain scale of 2 (mild) NRS.